2015
DOI: 10.1128/aac.00128-15
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Efficient Hepatic Delivery by Tenofovir Alafenamide (GS-7340) for Hepatitis B Virus Therapy

Abstract: Tenofovir alafenamide (TAF) is a prodrug of tenofovir (TFV) currently in clinical evaluation for treatment for HIV and hepatitis B virus (HBV) infections. Since the target tissue for HBV is the liver, the hepatic delivery and metabolism of TAF in primary human hepatocytes in vitro and in dogs in vivo were evaluated here. Incubation of primary human hepatocytes with TAF resulted in high levels of the pharmacologically active metabolite tenofovir diphosphate (TFV-DP), which persisted in the cell with a halflife … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
136
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(140 citation statements)
references
References 30 publications
1
136
1
2
Order By: Relevance
“…15 In vitro and in dogs, TAF had high intrahepatic extraction and enhanced levels of TFV-DP compared to TDF. 16 TAF 25 mg compared with TDF 300 mg has been studied in 2 global phase 3 HBV-monoinfected studies—one in treatment-naive or -experienced HBV e antigen (HBeAg)–negative participants (GS-US-320-0108) and one in monoinfected HBeAg-positive participants (GS-US-320-0110). Week 48 results were recently reported.…”
Section: Introductionmentioning
confidence: 99%
“…15 In vitro and in dogs, TAF had high intrahepatic extraction and enhanced levels of TFV-DP compared to TDF. 16 TAF 25 mg compared with TDF 300 mg has been studied in 2 global phase 3 HBV-monoinfected studies—one in treatment-naive or -experienced HBV e antigen (HBeAg)–negative participants (GS-US-320-0108) and one in monoinfected HBeAg-positive participants (GS-US-320-0110). Week 48 results were recently reported.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, tenofovir alafenamide (TAF) has been approved for the treatment of chronic HBV infection with compensated liver disease by the FDA in the US and has received a positive opinion from the Committee for Medicinal Products for Human Use, the scientific committee of the European Medicines Agency. This prodrug of tenofovir has demonstrated similar antiviral efficacy with improved renal and bone safety as compared to TDF, due to greater plasma stability and more efficient delivery of tenofovir to hepatocytes . Thus, in spite of our findings showing a high prevalence of HBV RASs at baseline in patients never treated with nucleoside/nucleotide analogues, it is possible to broadly achieve high rates of virological response, provided that the cascade of care is optimized.…”
Section: Discussionmentioning
confidence: 81%
“…While CatA is the main TAF-activating enzyme in most tissues, Ces1 may play an important role in metabolism of TAF in the liver. Indeed, Ces1 has recently been shown to be the main hydrolase responsible for TAF activation in the liver, with a minor contribution coming from CatA (35). Those authors showed an impaired metabolism of TAF in primary human hepatocytes in the presence of bis(4-nitrophenyl)phosphate (BNPP), a selective inhibitor of human carboxylesterase 1.…”
Section: Discussionmentioning
confidence: 98%